Electroencephalographic Reporting for Refractory Status Epilepticus. Issue 5 (September 2019) - Sansevere, Arnold J.; Arya, Ravindra; Sánchez Fernández, Iván; Gaillard, William D.; Tasker, Robert C.; Lai, Yi-Chen; Anderson, Anne E.; Tchapyjnikov, Dmitry; Chapman, Kevin E.; Brenton, J. Nicholas; Carpenter, Jessica L.; Gaínza-Lein, Marina; et al.
Abstract : Purpose: We aimed to determine whether clinical EEG reports obtained from children in the intensive care unit with refractory status epilepticus could provide data for comparative effectiveness research studies. Methods: We conducted a retrospective descriptive study to assess the documentation of key variables within clinical continuous EEG monitoring reports based on the American Clinical Neurophysiology Society's standardized EEG terminology for children with refractory status epilepticus from 10 academic centers. Two pediatric electroencephalographers reviewed the EEG reports. We compared reports generated using free text or templates. Results: We reviewed 191 EEG reports. Agreement between the electroencephalographers regarding whether a variable was described in the report ranged from fair to very good. The presence of electrographic seizures (ES) was documented in 46% (87/191) of reports, and these reports documented the time of first ES in 64% (56/87), ES duration in 72% (63/85), and ES frequency in 68% (59/87). Reactivity was documented in 16% (31/191) of reports, and it was more often documented in template than in free-text reports (40% vs. 14%, P = 0.006). Other variables were not differentially reported in template versus free-text reports. Conclusions: Many key EEG features are not documented consistently in clinical continuous EEG monitoring reports, including ES characteristics and reactivity assessment. Standardization may be needed for clinical EEG reports to provide informative data for large multicenter observational studies.